Linking Local Projects With Global Processes: Learning From Transdisciplinary Collaborations in African Cities - Patel, Zarina; Schneider, Flurina; Paulavets, Katsia (Frontiers in Sustainable Cities, 2022)
The central role of science and robust data sets as a means for advancing sustainable development has gained traction across science and policy communities globally. Furthermore, strengthening the science-policy interface in ways that link scientific knowledge production and societal problem solving requires both inter-disciplinary collaborations, as well as collaboration between researchers and extra-scientific actors. The paucity of data and understanding of the distinctive dynamics shaping Africa's urban transition provide an increasing impetus for engaging alternate and inclusive knowledge partnerships. Whilst the number of knowledge collaborations across African cities is increasing steadily, critical engagement with the practice of transdisciplinary approaches and the potential these alternate knowledge configurations might have for steering Africa's urban future(s) is limited. Drawing on the application of transdisciplinary approaches across 11 projects from the Leading Integrated Research for Agenda 2030 in Africa (LIRA 2030 Africa) programme on Advancing the implementation of SDG 11 in cities in Africa, this paper provides insights into the role of transdisciplinary approaches in bridging between local projects and global agendas. Evidence from the LIRA programme illustrates a positive relationship between carefully and purposefully constituted project teams who engage deeply with local contexts and the relevance of the resulting interventions. The common but differentiated experiences across the LIRA projects make it clear that the future of African urbanism is not singular but differentiated according to different local contexts. These projects simultaneously address the conceptual and service delivery deficits in local areas, whilst highlighting blind spots in global policy agendas that are misaligned to the complexity of African cities. The significance of transdisciplinary approaches that link the “what” to the “how” of urban change, is found to be critical in data poor post-colonial contexts, which are urgently in need of evidence-based policy reform shaping the reconfiguration of service delivery mechanisms. Finally, the significance of transdisciplinary research by early career scholars in and of Africa serves to shift the political economy of research on Africa, contributing to the transformative potential of urban experimentation in bridging between the global and the local.